Enantioselective Cyclopropanation of 2‐Cyano‐3‐arylacrylates Using Carbohydrate‐Based Crown Ethers. Issue 14 (7th April 2022) - Orbán, István; Varga, Bertalan; Bagi, Péter; Holczbauer, Tamás; Rapi, Zsolt
Abstract: Enantioenriched, highly functionalized cyclopropane derivatives were prepared by a simple and green approach using monosaccharide‐based chiral crown ethers as phase transfer catalysts. The Michael‐initiated ring closure (MIRC) reactions of diethyl bromomalonate with 2‐cyano‐3‐phenylacrylate took place with complete diastereoselectivity in the presence of chiral lariat ethers derived from carbohydrates and enantioselectivity up to 87 % ee was achieved. Among the catalysts tested, the monoaza‐15‐crown‐5 lariat ether having a methyl β‐d ‐glucopyranoside unit and a 2‐(3, 4‐dimethoxyphenyl)ethyl group on the nitrogen generated the highest asymmetric induction (87 % ee). In the reactions of analogous 2‐cyano‐3‐arylacrylates, enantioselectivity was in the range of 8–91 % ee. Abstract : Enantioenriched, highly substituted cyclopropane derivatives have been synthesized by the reaction of unsaturated cyanoacrylates with diethyl bromomalonate in the presence of carbohydrate‐based crown ethers under mild phase transfer catalytic conditions. The solvent and the aromatic moiety affected the enantioselecivity, and a correlation has been found between the asymmetric induction and the position of the substituents on the aromatic ring.